Earth wars : the battle for global resources - Hiscock, Geoff (Singapore ; Hoboken, NJ : John Wiley & Sons Singapore, 2012)
"A fascinating insight into the global battle for our energy future. The global competition for scarce natural resources that pits the West against the super-hot economies of China and India, plus a clutch of other contenders including Russia, Brazil, and Indonesia, has become one of the biggest issues facing the world today. Whether it is the rare metal lithium found in salt pans in the Andes, gas from the Caspian Sea, oil off the coast of Brazil, coal from Africa's Zambezi River, or uranium from Kazakhstan, China and India are desperate to ensure the security of their future energy supplies. The same goes for food and water, as contamination and over-use take their toll, the need to provide continued access for the next generation and beyond has increased exponentially. In Earth Wars: The Battle for Global Resources, international business journalist Geoff Hiscock explores the problems, potential solutions, and inevitable tensions in this ongoing scramble for finite natural resources"--Provided by publisher
The four essentials : food, water, energy, metals -- Geographical flashpoints : the trouble with lines on a map -- The key players : diggers, drillers, and dealers -- Food and water : where the rivers run -- "Going out" for energy : China and India stake their claims -- Old coal still burning brightly -- Going nuclear in a post-Fukushima world -- New energy -- clean, green, and expensive -- Coppery red, the colour of earth's true love -- Finding steel's essential ingredients -- U.S. energy : hail to the shale -- Japan after the deluge -- BRACQK (Brazil, Russia, Australia, Canada, Qatar, Kazakhstan) is the new BRIC -- The up and comers : Turkey, Iran, Indonesia, Mexico -- What happens next : a host of global opportunities -- Conclusion : a world so changed.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Natural resources -- Political aspects; Energy development -- Political aspects; Ressources naturelles -- Aspect politique; x -- Aspect politique; BUSINESS & ECONOMICS -- Real Estate -- General; Natural resources -- Political aspects